Spectroscopy advanced concepts - Penn, Jason (NY Research Press, 2015)
The onset of a new era of science has been marked by developments in spectroscopy and its functions. Spectroscopy scientists from various domains had been encouraged to share and discuss information that has been included in this book. It talks about latest developments in technology, functions and other advancements of spectroscopy. This book will augment the understanding of researchers about complications of different spectroscopic approaches and urge professionals and beginners to contribute part of their future research in understanding relevant mechanisms and applications of chemistry, physics and material sciences. Studies on analytical methods for determination of polyphenols, spectrophotometry and chemiluminometry, quality control of herbal medicines, flow-injection spectrophotometric analysis of Iron (II), Iron (III), and spectrophotometry as a tool for dosage sugars in nectar crops etc. are covered extensively in this book.